Knowledge Test for Extension Personnel on Rashtriya Krishi Vikas Yojana (Indian Journal of Extension Education, 2022)
Rashtriya Krishi Vikas Yojana is one of the massive agriculture development pan Indian programmes unleashed by Government of India requiring collective effort in unison from different agricultural line departments. The standard operating procedures and other nitty gritties of the programme should be clear to the department personnel implementing the same for its efficient reach. The study attempted to develop a Knowledge test comprising 21 items to measure knowledge level of Extension Personnel on Rashtriya Krishi Vikas Yojana during 2021-2022. The knowledge test was pretested on 30 extension personnel from other than the study area. The items with difficulty index ranging from 0.2 to 0.8, discrimination index above 0.1 and point biserial correlation which was significant at 5% level of significance were selected. The reliability of the test was measured by using split half method and was found to be 0.8. Eventually, 21 items were selected for the Knowledge test for extension personnel on Rashtriya Krishi Vikas Yojana.